Effect of antioxidants on the H(2)O(2)-induced premature senescence of human fibroblasts - Pieńkowska, Natalia (Aging (Albany NY), 2020)
The study was aimed at evaluation of the role of secondary oxidative stress in the stress-induced premature senescence (SIPS) of human fibroblasts induced by H(2)O(2). Two fibroblast lines were used: lung MRC-5 and ear H8F2p25LM fibroblasts. The lines differed considerably in sensitivity to H(2)O(2) (IC(50) of 528 and 33.5 μM, respectively). The cells were exposed to H(2)O(2) concentrations corresponding to IC(50) and after 24 h supplemented with a range of antioxidants. Most of antioxidants studied slightly augmented the survival of fibroblasts at single concentrations or in a narrow concentration range, but the results were not consistent among the cell lines. Chosen antioxidants (4-amino-TEMPO, curcumin, caffeic acid and p-coumaric acid) did not restore the level of glutathione decreased by H(2)O(2). Hydrogen peroxide treatment did not induce secondary production of H(2)O(2) and even decreased it, decreased mitochondrial potential in both cell lines and induced changes in the mitochondrial mass inconsistent between the lines. Antioxidant protected mitochondrial potential only in H8F2p25LM cells, but attenuated changes in mitochondrial mass. These results speak against the intermediacy of secondary oxidative stress in the SIPS induced by H(2)O(2) and suggest that the small protective action of antioxidants is due to their effects on mitochondria.